AKUNTABILITAS PROSES PELAYANAN PERSETUJUAN BANGUNAN GEDUNG (PBG) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN GOWA - Nasiratunnisaa Mallappiang; Rifdan; Hamsu Abdul Gani (Universitas Negeri Makassar, 2023)
This research is qualitative research with a phenomenological approach that aims to produce a strategy of the accountability for building approval services at the Gowa Regency. Informant selection was carried out by purposive sampling technique and data collection were used interview, observation, and documentation technique. The data analysis in this research was used the Miles and Huberman interactive models. The results of this study indicate that the process of public service accountability for Building Approvals at DPMPTSP Gowa Regency is considered not to be going well because there are still employees who do not follow procedures in providing PBG management services to applicants and there is no clarity of information and costs that are clearly displayed both on the SIMBG website page and those contained in the respective DPMPTSP agencies and the Gowa PUPR Service.